Frequency Adjustable Dual-Band Microstrip Gap-Ring-Slot Antenna Design Using the Cylindrical TLM Method - Tijana Z. Dimitrijevic; Jugoslav J. Jokovic; Nebojsa S. Doncov (Applied Computational Electromagnetics Society Journal (ACES), 2019)
This paper introduces a design of a frequency adjustable dual-band circular patch antenna with a gapring- slot accompanied by a study of a cylindrical TLM method effectiveness and capabilities. The antenna is fabricated on Rogers 4003 substrate and measured results have been used to validate the used approach. Through comparison with corresponding rectangular TLM mesh results, the cylindrical TLM method has been found not only as more efficient requesting much smaller number of cells to be applied but also more capable to accurately describe narrow ring slots and small angular features. The designed antenna resonates at two frequencies, 2.77 GHz and 3.72 GHz, with the possibility of additional frequency tuning. A frequency adjustments study has been carried out and, accordingly, design corrections have been proposed either to independently tune the frequency or to simultaneously adjust both frequencies.